Evaluating Mobile Palliative End-of-Life Advanced Care Enhancement (M-PEACE) Usability and Technology Acceptance: Mixed-Methods Design - Ni Luh Putu Inca Buntari Agustini; I Gede Putu Darma Suyasa; Israfil Israfil (Jurnal Keperawatan Indonesia, 2026)
Palliative End-of-Life Care (PEoLC) is a process requiring timely assessment, effective communication, and person-centered decision-making to support patients and families. Although the process can be strengthened through digital health innovations such as Mobile Palliative End-of-Life Advanced Care Enhancement (M-PEACE), its use in PEoLC remains limited. Therefore, this study aimed to evaluate M-PEACE usability and technology acceptance through an explanatory sequential mixed-methods design and explore user experiences in describing quantitative results. The quantitative phase was conducted to assess usability through an adapted System Usability Scale (SUS), and technology acceptance was measured using a modified Technology Acceptance Model (TAM) questionnaire. A total of 106 respondents (median age = 46.5 years) who participated were selected using convenience sampling. The results showed that internal consistency of the modified instruments was excellent (Cronbach’s α = 0.865–0.980). Quantitative analysis showed high agreement across usability, functionality, reliability, and transportability domains (median = 4). Perceived usefulness, ease of use, attitudes, behavioral intention, and trust were also high (median = 4–5). In line with the methodological procedures, the qualitative phase was conducted through semi-structured interviews with patients, family caregivers, and nurses to help explain and deepen the quantitative results. Thematic analysis identified three themes, namely (1) Positive Experience with the Application (user-friendly interface, easy access), (2) Perceived Benefits (motivation booster, better symptom monitoring, enhanced quality of life and dignity at end of life, improved self-care ability), and (3) Improvements Needed (reminders, simpler language, cross-platform access, additional tools, offline functionality). Overall, the integration of quantitative and qualitative results suggested that M-PEACE showed strong usability and acceptance, indicating substantial potential for incorporation into PEoLC service delivery.